Two Dimentional Numerical Models Of Hollow Fiber Membrane Contactor - N. Aryanti; Y. Bindar; I. G. Wenten (Dept. of Chemical Engineering, Diponegoro University, 2002)
Membrane contactor is separation processing unit using membrane as a contacting device. The major advantage of membrane contactor relies on its high contact area compared to conventional scrubber. One of the important applications of membrane contactor is to reduce emission of acid gases. In this work, modeling of membrane contactor is conductedto describe concentration distribution along fiber length used to predict effective fiber length by solving mass conservation equation. Solving of mass conservation equation required information of fluid flow distribution obtained by solving continuity and momentum equation simultaneously. The finite volume method is used to obtain the solution. Modeling of fluid flow was carried out by adding Darcy`s and Brinkman-Darcy flow models into Navier-Stokes equation. The momentum and continuity equation are solved for two-dimentional cylindrical coordinate. The result of velocity profile at axial direction were validated with Pangrle et.al. (1992) experimental data. The comparison shows that consideration using Brinkman-Darcy flow model give agood agreement with experimental data in which maximal axial velocity achieved is 0,047 m/s for this model and 0,05 m/s for experimental data.the concentration profile at radial direction using Darcy and Brickman-Darcy flow models have also been investigated. Furthermore, concentration profile at axial direction using the both two flow models indicate a decrease of concentration along fiber length. The comparison between models and experimental data by Subhakti and Azmier (1997) agree very closely to the Brinkman- Darcy flow model. The prediction of effective fiber length was conducted based on minimum economical flux oemembrane contactor. The calculation gives the effective fiber length obtained is 0.19 m at gas concentration, gas flow rate, and sorbent concentration of 0.02 mol/L, 0.8 m/s and 0.256 M respectively.Keywords : modeling, membrane contactor, Darcy, Brinkman-Darcy